The Effect of Service Quality on the Level of Guest Satisfaction at the Dairyland Riverside Resto Puncak, Bogor - Rivaldo, Aldo; Rainanto, Bambang Hengky (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Along with the times, competition in the business world is getting tougher. The existence of this competition requires business actors to be able to optimize the performance of their companies in order to be able to compete in market share. As for the company's way to be able to develop customer satisfaction such as the services provided and selling products at prices that match market share. Good presentation quality can also apply in attracting consumers. Good Quality Service will always exist in a company and will create pleasure for customers. After the customer feels pleasure with the goods received, of course the customer will compare the service that has been provided. This study aims to determine the effect of service quality on customer satisfaction that occurs at the Dairyland Riverside restaurant, Puncak, Bogor. In this study using a quantitative method in the form of a questionnaire. This sample was taken using purposive sampling and using the Slovin calculation method so that a sample of 96 respondents was obtained but rounded up to 100 respondents. Collecting data using a questionnaire and analyzed using multiple linear analysis. The results showed that service has an effect on customer satisfaction. Keywords: service quality, customer satisfaction.